Aggressive Angiomyxoma of the Vulva: A Bizarre Perineal Lesion - Adamantia Zizi-Sermpetzoglou; Despoina Myoteri; Kalliroi Koulia; Vassilios Kontostolis; Hippokratis Moschouris; Dionysios Dellaportas (Case Reports in Oncological Medicine)
Introduction. Aggressive angiomyxoma is a rare, slowly growing, and benign tumour of mesenchymal origin, which affects women of reproductive age and is associated with a high risk of local recurrence. Case Presentation. A case of a 47-year-old white female is presented herein, with a large polypoid, gelatinous mass on the right labia majora, measuring 26 × 21 × 6 cm. Histopathologically, the lesion was composed of spindle and stellate-shaped cells embedded in a myxoid matrix. Another specific feature was the presence of variable-sized thin-walled capillaries and thick-walled vascular channels. The patient underwent wide local excision of the tumour with clear margins and developed local recurrence 18 months later. Discussion. Aggressive angiomyxoma of the vulva needs to be distinguished from benign myxoid tumors with a low risk of local recurrence as well as from malignant myxoid neoplasms. Usually wide local excision with tumour-free margins and occasionally hormonal manipulation is the treatment of choice.